Analisis kesalahan penulisan pada abstrak skripsi berbahasa arab dalam perspektif kaidah Imla’ - Panagara, Fathi Hisyam; Ghofur, Mochamad Abdul; Bangki, Hasya Ramadina Lutfiyah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2023)
Writing an abstract thesis in 3 languages, Bahasa Indonesia, Arabic, and English, at the KH Institute. Abdul Chalim (IKHAC) Mojokerto is an effort to support the soft skills of its graduates. The purpose of this article was to evaluate the students’ writing skills (al-mahārah al-kitābah) through their Arabic abstract thesis. This article used a qualitative research approach with a literature study method. The study object is the theses of IKHAC students in 2020 that have been archived. Data analysis was conducted following Tarigan’s perspective on error analysis, while the indicators for analyzing errors in Arabic writing were based on the Imla’ rules from Ibrahim Khalil’s perspective. The results of the study indicate that the students of the Tarbiyah Faculty at IKHAC have advanced skills in Arabic writing skill. Further studies are expected to be conducted to assist in evaluating intensive Arabic language courses.